Case report: Rubella virus-induced cutaneous granulomas in a girl with atypical SCID caused by DCLRE1C gene mutations - Deng, Sihan; Rao, Shijia; Wang, Alun R.; Shi, Wei (Frontiers in Genetics, 2023)
Here, we report a case of rubella virus-induced granulomatous dermatitis in a young girl with immunodeficiency caused by DCLRE1C gene mutations. The patient was a 6-year-old girl who presented with multiple erythematous plaques on the face and limbs. Biopsies of the lesions revealed tuberculoid necrotizing granulomas. No pathogens could be identified on extensive special stains, tissue cultures, or PCR-based microbiology assays. Metagenomic next-generation sequencing analysis revealed the rubella virus. Underlying atypical severe combined immunodeficiency was recognized based on the patient’s history of repetitive infections since birth, low T-cell, B-cell, and NK cell counts, and abnormal immunoglobulins and complements. Whole-exome sequencing revealed the genetic abnormality of the atypical severe combined immunodeficiency (SCID), and compound heterozygous mutations of the DCLRE1C gene were detected. This report highlights the diagnostic values of metagenomic next-generation sequencing in identifying rare pathogens causing cutaneous granulomas in patients with atypical SCID.